Women of the Bible : a one-year devotional study of women in scripture - Spangler, Ann (Zondervan, 2015)
"Women of the Bible" focuses on the lives of fifty-two prominent and not-so-prominent women in Scripture to help you approach the story of salvation with fresh eyes. The updated and expanded edition of this bestselling book features refinements and new material designed to enhance its usefulness for both personal devotions and group study, including -- a list of all the women of the Bible -- a timeline of the women of the Bible -- a list of women in Jesus' family tree -- a list of women in Jesus' life and ministry. "Women of the Bible" offers a unique devotional program, combining five elements: inspiration, background information, Bible study, Bible promises, and prayer. Each week quickly becomes a personal or group retreat focused on the life of a particular woman. Vital and deeply human, the women in this book encourage through their failures as well as their successes. You'll see how God acts in surprising and wonderful ways to draw them--and you--to himself."--Back cover.